(7x -9)° + 4x° =

1 answer

To solve the equation (7x - 9)° + 4x° = 0, you would combine like terms and solve for x.

Starting with the left side of the equation:
(7x - 9)° + 4x° = 7x° - 9° + 4x°

Next, you would combine like terms:
7x° + 4x° - 9°

Now, you can simplify:
11x° - 9°

To solve for x, set the equation equal to 0 and isolate the variable:
11x° - 9° = 0

Add 9° to both sides:
11x° = 9°

Divide both sides by 11:
x° = 9°/11

The solution to the equation (7x - 9)° + 4x° = 0 is x° = 9°/11.